Funnel-web construction and estimated immune costs in Aglaoctenus lagotis (Araneae: Lycosidae) - González Pérez, María de la Macarena (2015)
Constructing webs for survival is rare in wolf spiders. However, some species, postulated as basal in the family, live in funnel-webs. Aglaoctenus lagotis (Holmberg 1876), a South American lycosid, lives permanently in webs. It is virtually unknown how web construction occurs for this species and the few other lycosid weavers. Also, costs associated with construction have not been studied, although funnels are suggested to be particularly costly webs. This study describes the funnel-web construction behavior of A. lagotis (Lycosidae: Sosippinae) and measures its costs in subadult and adult individuals. We recorded web construction, effects of sealing spinnerets in weaving activity, and immune costs of weaving (measuring melanization of an implant) in individuals allowed to weave and prevented from weaving. Construction consisted of three alternating behaviors: deposition of thick threads with a radial orientation and prolonged attachments (mainly involving the anterior spinnerets); deposition of swaths of fine threads without consistent orientation and with short attachments (mainly involving the posterior spinnerets); and motionlessness. No sticky threads are present in the web. The thick threads have a supporting function and the fine threads have a filling function. Subadults and males allowed to weave reduced their immune response compared with those prevented from weaving; no such relationship was observed for females. Males presented the weakest immune response, followed by subadults and females. The web construction process showed greater similarity with agelenid spiders than with the only other lycosid studied, Sosippus janus Brady 1972, and appears to be a costly activity, especially for males.